Need Analysis of Interactive Multimedia Based on Scientific Literacy in Physics Learning - Muhammad Arlim; Renol Afrizon; Hufri Hufri; Wahyuni Satria Dewi; Putri Dwi Sundari (Physics Learning and Education, 2023)
The 21st century requires the world of education to adjust the development of science and technology in improving the quality of education. However, there are several factors that occur in the field. First factor, the use of technology is not optimal as a medium for learning physics. The second factor, physics learning has not been implemented as needed. The third factor, the low scientific literacy of students. Following up on this, technology-based learning media such as interactive multimedia containing scientific literacy are needed. The first step in creating the media is a needs analysis. The purpose of this study was to obtain information on interactive multimedia needs analysis containing scientific literacy in physics subjects at Padang City Public High School. This type of research is descriptive research. The population of this research is all Padang City Public High School. The sampling technique is stratified random sampling and lottery techniques. So that the samples were obtained from three Padang public high schools. Data collection techniques using learning style instruments and instruments for student and teacher needs. This study uses descriptive statistical analysis techniques. The results showed that the student's learning style was 81%, the category was very high. The student's need for interactive multimedia containing scientific literacy is 97% very high category and the teacher's need for interactive multimedia containing scientific literacy is 100% very high category. The conclusion of this study is the need to develop interactive multimedia based on scientific literacy in physics subjects at Padang public high school.